2001
DOI: 10.1177/135965350100600104
|View full text |Cite
|
Sign up to set email alerts
|

Virological Response in Multidrug-Experienced HIV-1-Infected Subjects Failing Highly Active Combination Regimens after Shifting from Lamivudine to Didanosine

Abstract: The aim of this study (the RESCUE trial) was to verify the effect of a shift from a lamivudine-containing to a didanosine-containing regimen on viral replication in HIV-1-infected subjects who had experienced prior treatment failure. Sixteen patients (didanosine-experienced in 14/16 cases) were consecutively enrolled: eight patients shifted from lamivudine to didanosine without other changes in their drug regimen. The other eight shifted from lamivudine to didanosine and changed one or more of their other drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…2a In the presence of thymidine analogue mutations (TAMs), M184V decreases susceptibility to zidovudine, stavudine, and tenofovir. 6 On the other hand, T215Y mutation on its own results in intermediate (10-to 15fold) zidovudine resistance. 7 The Q151M complex or multidrug resistance (MDR) mutation (A62V, V75I, F77L, F116Y, and Q151M) has been shown to confer cross-resistance to most of the NRTIs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2a In the presence of thymidine analogue mutations (TAMs), M184V decreases susceptibility to zidovudine, stavudine, and tenofovir. 6 On the other hand, T215Y mutation on its own results in intermediate (10-to 15fold) zidovudine resistance. 7 The Q151M complex or multidrug resistance (MDR) mutation (A62V, V75I, F77L, F116Y, and Q151M) has been shown to confer cross-resistance to most of the NRTIs.…”
mentioning
confidence: 99%
“…However, during the long-term therapy, resistance to chemotherapy can develop in a significant number of patients. In recent years, resistance data from clinical trials have revealed important information on the patterns, prevalence, and effects of resistance seen among patients experiencing virologic failure. The prevalence of some mutations such as M184V and Q151M has remained relatively constant, while the L74V mutation, the 69 insertions, and thymidine analogue mutations have decreased in prevalence. Other mutations such as K65R and Y115F, while still relatively uncommon, are increasing in prevalence.…”
mentioning
confidence: 99%
See 1 more Smart Citation